Expression of Pili Genes (ebpA and ebpC) Associated with Multi Drug Resistant Enterococcus faecalis Isolates - May Talib Flayyih; Ayat Ahmed Najm (College of Pharmacy University of Baghdad, 2024)
The antibiotic susceptibility was determined for 118 clinical E. faecalis isolates , the isolates showed various levels of susceptibilities to different antibiotics and 70.5% of these isolates were multidrug resistant. The relative expression of ebpA gene in six multidrug resistance E. faecalis isolates was determined in comparison with antibiotic-sensitive isolates selected as a control sample. The isolate 21 from root canal (multi drug resistance) showed increasing in expression in comparison with antibiotic sensitive isolates of E. faecalis. The relative expression of ebpC gene in multidrug resistance E. faecalis isolates was determined in comparison with antibiotic sensitive isolates which were selected as control samples. The isolate 21 from root canal and the isolates 19 from urine (multi drug resistance) showed high expression in comparison with antibiotic sensitive isolates of E. faecalis. The expression of ebpA and ebpC genes in multi drug resistance isolates in relation to their sources showed that urine group gave a high rate of expression of ebpC followed by root canal in comparison with ebpA expression. In contrast, the vagina group gave a higher expression of ebpA than ebpC. The findings of the present investigation revealed a significant correlation (P=0.05) between the multi-drug resistance and gene expression of ebpA gene, while there is no significant (P=0.05) correlation with ebpC.